A Solid Film Electrode of Intermetallic Ag 2 Hg 3.02 for the Direct Determination of Folic Acid in Fresh and Processed Fruit Juices - Paula, Cleide Garcia de; Toledo, Renata Alves de; Vaz, Carlos Manoel Pedro; Cordeiro, Paulo Jorge Marques; Batistuti, José Paschoal; Pastre, Ieda Aparecida; Shim, Hojae; Fertonani, Fernando Luís Fertonani [UNESP] (Wiley, 2014)
AgSIE was used for the direct analysis of folic acid (FA), with a detection limit and lower level of quantitation of 6.8 x10-10 mol L-1 and 2.3 x 10 8 mol L-1. The analysis in fresh and processed fruits was done without any sample pretreatment. In strawberry and acerola juices, FA concentration level values were below the method detection limit. FA was detectable in peach (77.7 0.4 mg L-1 and 64.4 0.5 mgL-1), Persian lime (45.4 0.7 mg L-1), pineapple Hawaii (66.2 0.4 mgL-1), pear pineapple (35.3 0.6 mgL-1), cashew (54.4 0.5 mgL-1) , passion fruit (73.2 0.3 mgL-1), and apple (84.4 0.5 mg L-1 ).
Keywords: Determination the folic acid; Fruit Juices; SWAdSV; Intermetallic Ag 2 Hg 3.02; SEM images; XRD